Nonlinear optical materials by electrospinning technique. Issue 20 (14th May 2014) - De Matteis, Fabio; Fanicchia, Francesco; Lamastra, Francesca Romana; Stracci, Glauco; De Angelis, Roberta; Prosposito, Paolo; Nanni, Francesca; Casalboni, Mauro
ABSTRACT The possibility of using electrospinning to deposit, and simultaneously electrically pole, polymeric mats containing nonlinear optical (NLO) molecules is studied. Disperse Red 1 (DR1) chromophore dispersed into polymethyl methacrylate (PMMA) fibers is chosen as test system. Aligned fibers of DR1/PMMA are deposited by means of the rotating collector electrospinning technique. The processing parameters are optimized to obtain an oriented texture of fibers and the NLO activity is characterized by means of second harmonic generation measurements. Comparison with spin coating and corona poling samples of the same material is discussed. The results point toward a low efficiency of chromophore orientation for the electrospun samples in comparison to the poled ones. An improvement in the electrospinning apparatus is proposed to enhance the chromophore orientation in the polymeric fibers. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40913.